Hot Air Balloons on Empty Field East of Fort Washington Road - Watkins, Howard::::::::: (1986)
Several different balloons being inflated; Gregory Leifer wearing LA Dodgers cap and pointing; Christine Watkins holding Adam Watkins in red shirt